Business analytics for managers : taking business intelligence beyond reporting - Laursen, Gert H. N.; Thorlund, Jesper (Hoboken, N.J. : Wiley, 2010)
"Many companies are unsure exactly what business analytics is and how it can be used to improve their performance. Much of the material currently in the marketplace is technical in nature. This book's focus is not on the technical aspects of business analytics but takes a business holistic approach. It provides an explanation of what business analytics is and how it should be important to people in sales, marketing, management, finance, HR, production as well as analysis and controlling. This book provides a business analytics model that focuses on the interaction of IT technology, strategy, business processes, and a broad spectrum of human competencies, organizational circumstances, and cooperation across the organization. This book will be comprised of nine chapters: (1) The Business Analytics Model; (2) Business Analytics at the Strategic Model; (3) Development and Deployment of Information at a Functional Level; (4) Business Analytics at an Analytical Level; (5) Business Analytics at the Data Warehouse Level; (6) The Company's Collection of Source Data; (7) The Structuring of a Business Intelligence Competency Center; (8) Assessment and Prioritization of Business Analytics Projects; and (9) Business Analytics in the Future."--
Includes index.
Keywords: Business intelligence